2018
DOI: 10.48550/arxiv.1809.04075
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An All-Sky Search For R Coronae Borealis Stars in ASAS-SN

J. V. Shields,
T. Jayasinghe,
K. Z. Stanek
et al.

Abstract: We report the discovery of 19 new R Coronae Borealis (RCB) star and DY Per candidates with light curves from the All-Sky Automated Survey for Supernovae (ASAS-SN). We examined both an existing set of 1602 near/mid-IR selected candidates and an additional 2615 candidates selected to have near/mid-IR SEDs consistent with those of known R Coronae Borealis stars. We visually inspected the light curves for the characteristic variability of these systems.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…We also identified two other R Coronae Borealis (RCB) candidates during the analysis of the SR/IRR class (ASASSN-V J 043259.32+415854.0, ASASSN-V J 175700.51-213934.5). These sources and 17 other RCB candidates discovered in ASAS-SN are discussed in Shields et al (2018).…”
Section: Rare Variablesmentioning
confidence: 99%
“…We also identified two other R Coronae Borealis (RCB) candidates during the analysis of the SR/IRR class (ASASSN-V J 043259.32+415854.0, ASASSN-V J 175700.51-213934.5). These sources and 17 other RCB candidates discovered in ASAS-SN are discussed in Shields et al (2018).…”
Section: Rare Variablesmentioning
confidence: 99%
“…We have also explored the synergy between ASAS-SN and APOGEE (Holtzman et al 2015) with the discovery of the first likely non-interacting binary composed of a black hole with a field red giant (Thompson et al 2018) and a detailed variability analysis of the APOGEE sources to identify 1914 periodic variables (Pawlak et al, in prep). We have also identified rare variables, including 2 very long period detached eclipsing binaries (Jayasinghe et al 2018c,d) and 19 R Coronae Borealis stars (Shields et al 2018) .…”
mentioning
confidence: 90%
“…We have also explored the synergy between ASAS-SN and APOGEE (Holtzman et al 2015) with the discovery of the first likely non-interacting binary composed of a black hole with a field red giant (Thompson et al 2018) and we identified 1924 APOGEE stars as periodic variables in Paper IV (Pawlak et al 2019). We have also identified rare variables, including 2 very long period detached eclipsing binaries (Jayasinghe et al 2018b,c) and 19 R Coronae Borealis stars (Shields et al 2018).…”
mentioning
confidence: 89%